Flexible neural electrode composite coating as well as preparation method and application thereof
By preparing flexible composite coatings on nerve electrodes, using nanofibers and conductive polymer modifications, combined with the biocompatibility of hydrogels, the problems of electrochemical impedance and inflammatory response of implanted nerve electrodes in the body are solved, and the problem of electrochemical impedance and inflammatory response of implanted nerve electrodes is achieved. High-quality electrophysiological signal recording and long-term stability.
Patent Information
- Application Number
- CN202411626118.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
Existing implantable neural electrodes face problems of increased electrochemical impedance and inflammatory response when used in vivo, resulting in reduced signal detection quality and electrode failure.
Using flexible nerve electrode composite coating, including polycaprolactone (PCL) and methacrylylated silk fibroin (SFMA) nanofibers, conductive polymer poly3,4-ethylenedioxythiophene (PEDOT) Modified in situ and covered with methacrylylated silk fibroin hydrogel to form a composite coating of nanostructures.
By reducing electrode impedance and reducing inflammatory response, signal quality and long-term stability of the electrode are improved, and high-quality electrophysiological signal recording is achieved.
Smart Images

Figure CN119499460A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials and relates to a flexible neural electrode composite coating and a preparation method and application thereof. Background Art
[0002] Neural electrodes are devices that can detect and regulate neural networks and are an important bridge for information exchange between the body and external devices. As the only interface that can currently record electrophysiological signals of single neuronal cells, the efficiency and quality of signal recording of implantable neural electrodes still need to be improved. With the development of implantable neural electrode technology, significant progress has been made in the size, channels, and density of electrodes to improve spatial accuracy during recording or stimulation. However, there are still two major challenges that hinder the in vivo application of implantable neural electrodes.
[0003] First, the size of neural electrodes has been continuously reduced in recent years. Although this can achieve higher spatial resolution, the reduction in the working area of the electrode causes a significant increase in electrochemical impedance, which affects the quality of subsequent electrophysiological signal detection. Secondly, neural electrode implantation usually causes acute and long-term inflammatory responses, resulting in the encapsulation of the neural electrode surface by glial scars and neuronal cell death, which ultimately causes the implanted neural electrodes to lose the ability to record and stimulate in vivo. Therefore, it is necessary to design and develop neural interfaces that have both suitable electrochemical properties and excellent biocompatibility to improve the ability of long-term implanted electrodes to effectively record neural signals.
[0004] Modifying the electrode surface with a conductive polymer (CP) can increase the surface roughness of the microelectrode, thereby improving the electrochemical performance and biocompatibility of the microelectrode. Due to the limited specific surface area and electrochemical active area of conventional conductive polymer films, it is necessary to develop conductive polymers with nanostructures. In addition, nanostructured coatings have also been shown to support the attachment and differentiation of neural cells. Therefore, conductive polymers with nanostructures are of great significance in the field of brain-computer interfaces. The excellent electrochemical properties and porous structure enable the corresponding microelectrodes to have better neural signal recording performance.
[0005] The use of flexible substrate materials and modifications of conductive polymers has improved the mechanical mismatch problem between traditional implantable neural electrodes and tissues to a certain extent. Due to its superior chemical-mechanical similarity with biological tissues, hydrogels have become one of the strong candidate materials for the interface between organisms and systems. In the field of brain-computer interfaces, further manufacturing more integrated conductive polymer-hydrogel composites while giving full play to the excellent properties of both, minimizing tissue damage and inflammatory responses while achieving high-quality and long-term stable signal recording, is an important research direction. In addition, adding anti-inflammatory drugs to the composite system to obtain better anti-inflammatory effects is also one of the commonly used strategies.
[0006] In this work, we demonstrated a hybrid multifunctional neural microelectrode coating to detect high-quality electrophysiological signals stably and over a long period of time in vivo. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a flexible neural electrode composite coating and its preparation method and application. The flexible neural electrode composite coating of the present invention can reduce the inflammatory response after the neural electrode is implanted in the body, and at the same time, the electrode impedance is greatly reduced by using a conductive polymer with a nanostructure, thereby having a higher cathode charge storage capacity. Through the synergistic effect of the two factors, the tissue inflammatory response is reduced, the signal quality is improved, and the stable collection of long-term in vivo electrophysiological signals is achieved.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] On the one hand, the present invention provides a flexible neural electrode composite coating, which includes: polycaprolactone (PCL) containing anti-inflammatory drugs and methacryloylated silk fibroin (SFMA) nanofibers, the surface of the nanofibers is in situ modified with a conductive polymer poly-3,4-ethylenedioxythiophene (PEDOT), and the surface of the modified material has a cured methacryloylated silk fibroin (SFMA) hydrogel.
[0010] In the neural electrode composite coating, the conductive polymer with nanofibers as template significantly improved the electrochemical performance of the bioelectronic device; the introduction of the anti-inflammatory drug minocycline alleviated the tissue inflammatory response; the addition of hydrogel further improved the biocompatibility, reduced the adhesion of inflammatory factors, and reduced the Young's modulus, forming an effective buffering effect with the brain tissue, thereby giving the bioelectronic coating long-term stability.
[0011] The anti-inflammatory drug is selected from minocycline (MH) or dexamethasone.
[0012] Preferably, the polymer is selected from any one of polycaprolactone, polylactic acid or polylactic acid-co-glycolic acid or a combination of at least two thereof.
[0013] In another aspect, the present invention provides a method for preparing the flexible neural electrode composite coating as described above, the preparation method comprising the following steps:
[0014] (1) a solution containing a polymer, methacrylylated silk fibroin, and an anti-inflammatory drug is electrospun into nanofibers, which are then received on a flexible electrode surface;
[0015] (2) immersing the flexible electrode receiving the nanofibers obtained in step (1) in an electrodeposition solution containing 3,4-ethylenedioxythiophene (EDOT), and performing in-situ electrodeposition by constant current deposition to in-situ modify the conductive polymer poly (3,4-ethylenedioxythiophene) on the surface of the nanofibers;
[0016] (3) coating the surface of the in-situ modified flexible electrode obtained in step (2) with methacrylylated silk fibroin hydrogel solution and solidifying it into a gel to obtain the flexible neural electrode composite coating.
[0017] Preferably, the solvent in the solution of step (1) is any one of hexafluoroisopropanol, chloroform or dimethyl sulfoxide, or a combination of at least two thereof.
[0018] Preferably, the sum of the weight percentage concentrations of the polymer and the methacryloylated silk fibroin in the solution of step (1) is 11-13%, for example, 11%, 11.5%, 12%, 12.5% or 13%. In the present invention, if the weight percentage concentration of the polymer in the solution is too low or too high, it will affect the morphology of the nanofibers. Low concentration may cause the surface tension of the dilute polymer solution to be large and the molecular entanglement to be low, so that droplets instead of fibers are obtained during the electrospinning process; high concentration leads to high viscosity of the mixed solution, and the jet formed during the electrospinning process may be difficult to break into fibers, which may cause adhesion between fibers or form a beaded structure. In addition, high concentration of electrospinning solution may cause the fiber diameter to increase because the increase in solution viscosity limits the stretching effect of the electric field on the jet.
[0019] Preferably, the mass ratio of the polymer, methacrylylated silk fibroin and the anti-inflammatory drug minocycline in the solution of step (1) is 5-7:5:1, for example 5:5:1, 5.5:5:1, 6:5:1, 6.5:5:1 or 7:5:1.
[0020] In the present invention, when preparing the solution in step (1), polycaprolactone, methacrylylated silk fibroin and the anti-inflammatory drug minocycline are added to a solvent and stirred at room temperature until a mixture with uniform color is obtained.
[0021] Preferably, the base material of the flexible electrode in step (1) includes polyimide (PI), polyurethane (TPU) and SU-8, etc.
[0022] Preferably, the conditions for the electrospinning in step (1) are: a voltage of 16-18 kV (e.g., 16 kV, 16.5 kV, 17 kV, 17.5 kV or 18 kV), a distance between the needle tip and the receiver of 8-12 cm (e.g., 8 cm, 9 cm, 10 cm, 11 cm or 12 cm), and a pump speed of 0.6-0.9 mL / h (e.g., 0.6 mL / h, 0.7 mL / h, 0.8 mL / h or 0.9 mL / h).
[0023] In the present invention, after the step (1) is received on the surface of the flexible electrode, the electrode is placed in a cool place for 1 day to evaporate excess solvent.
[0024] Preferably, the solvent in the electrodeposition solution in step (2) is water.
[0025] Preferably, the molar concentration of 3,4-ethylenedioxythiophene in the electrodeposition solution is 0.1 mM.
[0026] Preferably, the electrodeposition solution in step (2) also includes an auxiliary agent.
[0027] Preferably, the auxiliary agent is selected from any one of LiClO4, polystyrene sulfonic acid or carbon nanotubes, or a combination of at least two thereof.
[0028] Preferably, the molar concentration of the auxiliary agent in the electrodeposition solution is 0.01-0.02 mM.
[0029] Preferably, in the step (2), the electrodeposition solution is prepared by dissolving the solute in the solvent through ultrasound.
[0030] Preferably, the ultrasound time is 30-45 min, for example, 30 min, 33 min, 35 min, 38 min, 40 min, 42 min or 45 min.
[0031] In the present invention, the electrodeposition solution can be prepared and used immediately, and needs to be stored in a 4° C. refrigerator away from light, and should be ultrasonicated for 30 minutes before each use.
[0032] Preferably, the voltage of the in-situ electrodeposition in step (2) is 1-1.1 V, and the deposition time is 100-350 s (e.g., 100 s, 130 s, 150 s, 180 s, 200 s, 250 s, 280 s, 300 s or 350 s).
[0033] Preferably, the mass percentage concentration of methacrylylated silk fibroin in the methacrylylated silk fibroin hydrogel solution in step (3) is 12-15%, such as 12%, 13%, 14% or 15%.
[0034] Preferably, the methacrylylated silk fibroin hydrogel solution in step (3) further comprises a photoinitiator.
[0035] Preferably, the photoinitiator is selected from lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0036] Preferably, the mass percentage concentration of LAP in the methacrylylated silk fibroin hydrogel solution is 0.1%.
[0037] Preferably, the coating in step (3) is performed by spin coating.
[0038] In the present invention, the spin coating is performed using a spin coater. Preferably, the spin coating is performed at a low speed of 100-200 r / s (e.g., 100 r / s, 120 r / s, 150 r / s, 180 r / s or 200 r / s) for 5-10 s (e.g., 5s, 6s, 7s, 8s, 9s or 10s), and at a high speed of 500-700 r / s (e.g., 500 r / s, 550 r / s, 600 r / s, 650 r / s or 700 r / s) for 5-10 s (e.g., 5s, 6s, 7s, 8s, 9s or 10s).
[0039] On the other hand, the present invention provides a flexible neural electrode, comprising a flexible electrode and the flexible neural electrode composite coating as described above covering the outer surface of the flexible electrode.
[0040] On the other hand, the present invention provides the use of the flexible neural electrode composite coating or the flexible neural electrode as described above in the long-term acquisition of electrophysiological signals for non-therapeutic and non-diagnostic purposes.
[0041] The flexible neural electrode composite coating or the flexible neural electrode of the present invention can detect anti-inflammatory effects and perform long-term collection of electrophysiological signals.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1) The present invention significantly improves electrochemical performance and biocompatibility: In the neural electrode composite coating prepared by the present invention, the conductive polymer with nanofibers as template significantly improves the electrochemical performance of the bioelectronic device; the introduction of the anti-inflammatory drug minocycline reduces tissue inflammatory response; the addition of hydrogel further improves biocompatibility, reduces the attachment of inflammatory factors, and reduces Young's modulus, forming an effective buffering effect with brain tissue, thereby making the bioelectronic coating have long-term stability.
[0044] 2) The present invention improves signal recording and stimulation capabilities: The neural electrode composite coating prepared by the present invention has excellent performance, constructs a mechanically stable intermediate buffer layer structure, and enhances the stimulation and recording capabilities of the electrode; the composite coating achieves high charge storage / injection capacity, low interface impedance and good biocompatibility; it can stably record dynamic single neuron signals for a long time, ensuring high-quality acquisition of in vivo electrophysiological signals.
[0045] In summary, the present invention provides an invasive flexible neural electrode composite coating with significant anti-inflammatory effect, excellent electrochemical properties and long-term stability, which provides reliable technical support for the clinical application of neural electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a high-resolution scanning electron microscope image of the conductive polymer in the neural electrode composite coating of the present invention;
[0047] Figure 2 This is a high-resolution scanning electron microscope image of the hydrogel in the neural electrode composite coating of the present invention;
[0048] Figure 3 The cyclic voltammogram and cathode charge storage diagram of the neural electrode composite coating of the present invention;
[0049] Figure 4 The impedance diagram of the neural electrode composite coating of the present invention;
[0050] Figure 5 This is a live-dead staining fluorescence image of the neural electrode composite coating modified by the present invention.
[0051] Figure 6 It is an in vivo inflammatory immunofluorescence image after modification of the neural electrode composite coating of the present invention;
[0052] Figure 7 This is a comparison diagram of the original electrophysiological signals after the neural electrode composite coating of the present invention is modified;
[0053] Figure 8 A comparison diagram of single neuron signals after modification of the neural electrode composite coating of the present invention;
[0054] Fig. 9 This is a comparison diagram of the signal-to-noise ratio of the neural electrode after the composite coating of the present invention is modified. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] Example 1
[0057] A flexible neural electrode composite coating with long-term anti-inflammatory properties and a preparation method thereof, specifically comprising the following steps:
[0058] 1) 0.06 g of polycaprolactone (PCL, Prucitan) with a molecular weight of 80,000, 0.06 g of SFMA and 0.012 g of minocycline were mixed in 1 mL of hexafluoroisopropanol and stirred at room temperature until a mixture with uniform color was obtained;
[0059] 2) spinning the mixture in step 1) into nanofibers by electrospinning and modifying the flexible electrode and the conductive glass ITO surface at the flat plate receiver below; the electrospinning conditions are: voltage of 18 kV, distance between the needle tip and the receiver of 10 cm, and pump speed of 0.8 mL / h;
[0060] 3) Place the modified flexible electrode and ITO in a cool place for 1 day to evaporate excess solvent;
[0061] 4) ultrasonically dissolving 0.1 mM EDOT and 0.02 mM LiClO4 in deionized water to prepare an electrodeposition solution;
[0062] 5) immersing the modified flexible electrode and ITO in the electrodeposition solution in 4), and in-situ electrodeposition of the modified conductive polymer is performed by constant current deposition method, wherein the voltage E is 1 V and the deposition time is 300 s;
[0063] 6) Dissolving SFMA and LAP in deionized water to prepare a hydrogel solution, wherein the mass fraction of SFMA is 12% and the mass fraction of LAP is 0.1%, and the electrode in step 5) is evenly covered with the gel solution using a spin coater, and then cured by ultraviolet light for 1 minute to obtain the flexible neural electrode composite coating.
[0064] The performance of the material prepared in Example 1 was verified.
[0065] Sterilization treatment: The prepared ITO, ITO / PCLSFMA, ITO / PCLSFMA-MH (MH mass concentration is 5%, 10%, 15%) and ITO / PCLSFMA-MH / GEL samples were placed under ultraviolet light for 12 hours for sterilization. Among them, ITO refers to conductive glass, ITO / PCLSFMA refers to a layer of PCLSFMA nanofibers modified on the surface of ITO, ITO / PCLSFMA-MH refers to PCLSFMA with MH modified on the surface of ITO, and ITO / PCLSFMA-MH / GEL refers to a layer of hydrogel spin-coated after the previous sample.
[0066] Cell preparation: Take HT22 neuronal cells from the mouse hippocampus in the logarithmic growth phase and adjust the cell density to 3×10^4 cells / mL. Add 1 mL of cell suspension to each well of the well plate and place it in an incubator for pre-culture for 12 hours (37°C, 5% CO2). Sample culture: Aspirate the pre-culture medium, add samples ITO, ITO / PCLSFMA, ITO / PCLSFMA-MH (5, 10, 15) and ITO / PCLSFMA-MH / GEL, and then add 1 mL of culture medium for culture. Take out the samples after 24 hours and 48 hours, follow the steps of the CCK-8 kit, and use the microplate reader SpectraMax M3 (Molecular Devices) to test the absorbance at a wavelength of 450 nm.
[0067] Cytotoxicity test: After the samples were pre-cultured in an incubator for 12 h (37° C., 5% CO 2 ), the pre-culture medium was aspirated and the cells were washed three times with basal medium.
[0068] Staining and imaging: 1 μL of Calcein-AM / Propidium iodide (PI) was diluted 1000 times with F12 basal medium and incubated for 20 min. The cells were washed twice with basal medium and photographed under a confocal microscope.
[0069] Figure 1 This is a high-resolution scanning electron micrograph (Quanta, FEG 250) of the conductive polymer in the neural electrode composite coating prepared in Example 1. It can be seen that the neural electrode is first evenly covered with a layer of PCLSFMA nanofibers, and then a layer of PEDOT is grown on the surface of the electrode point. The PEDOT is wrapped around the surface of the nanofibers to form a PEDOT-PCL nanocore-shell structure with a large specific surface area.
[0070] Figure 2 This is a scanning electron microscope image of the SFMA hydrogel in the invasive flexible nerve electrode composite coating prepared in Example 1. The hydrogel coating has a uniform thickness.
[0071] Figure 3 The cyclic voltammogram of the invasive flexible neural electrode composite coating prepared in Example 1. The electrochemical properties of the gold electrode point (square), the electrode point loaded with PCLSFMA nanofibers (circle), the electrode point further modified with PEDOT (equilateral triangle) and the electrode point finally modified with SFMA hydrogel (inverted triangle) are characterized respectively. The increase in the curve area proves that the electrochemical performance of the electrode after modification with PEDOT is greatly improved, and the electrochemical performance after modification with non-conductive SFMA hydrogel is not greatly affected.
[0072] Figure 4The impedance diagram of the invasive flexible neural electrode composite coating prepared in Example 1. The electrochemical impedance of the gold electrode point (square), the electrode point loaded with PCLSFMA nanofibers (circle), the electrode point further modified with PEDOT (equilateral triangle) and the electrode point finally modified with SFMA hydrogel (inverted triangle) are characterized. At 1000 Hz, the impedance of the electrode modified with PEDOT is 1-2 orders of magnitude lower than that of the unmodified electrode, and the modification of the non-conductive SFMA hydrogel does not increase the impedance of the electrode.
[0073] Figure 5 The cell live and dead staining image of the invasive flexible neural electrode composite coating prepared in Example 1. The live and dead staining of biological cells when the concentration of SFMA was 15% (GEL15) and the concentration of MH was 20% (MH20) were investigated respectively. Compared with the control group, there were basically no dead cells in both experimental groups, and the cell density was similar to that of the control group, proving that the composite coating has good biocompatibility.
[0074] Figure 6 This is a long-term immunofluorescence image of the invasive flexible neural electrode composite coating prepared in Example 1.
[0075] DAPI represents cell nuclei, GFAP represents astrocytes, NeuN represents neurons, and Merge represents the superposition of three fluorescence images. Compared with the control group, GFAP in the experimental group showed weaker fluorescence and NeuN showed stronger fluorescence, which proves that the modification of the composite coating can reduce tissue inflammation.
[0076] Example 2
[0077] A flexible neural electrode composite coating with long-term anti-inflammatory properties and a preparation method thereof, specifically comprising the following steps:
[0078] 1) 0.11 g of polycaprolactone (PCL, Prucitan) with a molecular weight of 80,000, 0.11 g of SFMA and 0.022 g of minocycline were mixed in 2 mL of hexafluoroisopropanol and stirred at room temperature until a mixture with uniform color was obtained;
[0079] 2) spinning the mixture in step 1) into nanofibers by electrospinning and modifying the surface of the flexible electrode at the flat plate receiver below; the electrospinning conditions are: voltage of 17 kV, distance between the needle tip and the receiver of 10 cm, and pump speed of 0.7 mL / h;
[0080] 3) Place the modified flexible electrode in a cool place for 1 day to evaporate excess solvent;
[0081] 4) ultrasonically dissolving 0.1 mM EDOT and 0.02 mM LiClO4 in deionized water to prepare an electrodeposition solution;
[0082] 5) immersing the modified flexible electrode in the electrodeposition solution in 4), and in-situ electrodeposition of the modified conductive polymer is performed by constant current deposition method; the voltage E is 1.1 V, and the deposition time is 100 s;
[0083] 6) Dissolve SFMA and LAP in deionized water to prepare a hydrogel solution, wherein the mass fraction of SFMA is 15% and the mass fraction of LAP is 0.1%. Use a spin coater to evenly cover the electrode in step 5) with the gel solution, and then cure it under ultraviolet light for 1 minute to obtain a flexible neural electrode composite coating.
[0084] The performance of the material prepared in Example 2 was verified.
[0085] Electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV) tests
[0086] Electrolytic cell: 0.01 M phosphate buffered saline (PBS);
[0087] A conventional three-electrode configuration was used, with a platinum electrode as the counter electrode and a silver / silver chloride electrode as the reference electrode;
[0088] The scanning potential of CV was between -0.8 and 0.8 V, and the scanning rate was 100 m V / s.
[0089] Detailed steps for implanting flexible electrodes in mice:
[0090] Anesthesia: Prepare a 1% sodium phenobarbital solution and inject approximately 100 μL into 4-week-old C57 male mice to ensure complete anesthesia.
[0091] Fix the mouse: Fix the fully anesthetized mouse on the stereotaxic instrument to ensure that the brain is stable and level. Adjust the stereotaxic instrument to ensure that the brain is stable and the height difference between the two sides is less than 0.1.
[0092] Head preparation: Use scissors to cut the skin on the head and use tweezers to pick away the mucous membrane on the surface of the skull to prevent the scalp from being rolled away when the cranial drill is used later.
[0093] Skull drilling: Use a skull drill to drill holes in four places on the head, making sure the skull has been opened without damaging the brain tissue, and then use a fine needle tip to pierce the dura mater. Keep it moist during the process and moisten the skull with saline regularly.
[0094] Electrode implantation: Align the reserved hole at the bottom of the flexible electrode with the skull hole, use the implantation needle under the microscope to slowly lower the electrode to a scale of about -1.7, pull out the needle, and leave the electrode in the brain.
[0095] Sealed electrodes: Electrodes were sealed inside the mouse brain using dental cement.
[0096] Skull pin fixation (long-term observation requirement): If long-term observation is required, the number of implanted electrodes is reduced to 2, and the extra skull holes are fixed with skull pins. The skull pins need to be rotated and 1 / 3 of them should be kept outside the bone to ensure fixation without damaging the brain.
[0097] Figure 7 The original electrophysiological signal comparison diagram of the invasive flexible neural electrode composite coating prepared in Example 2. The original signal diagram of the experimental group has obvious spike signals, higher signal amplitude and lower noise. The selected spike single representative diagram also further illustrates that the signal amplitude collected by the modified electrode is more obvious and has a higher signal-to-noise ratio.
[0098] Figure 8 This is a comparison chart of the average waveforms of the invasive flexible neural electrode composite coating prepared in Example 2. The average waveform of the experimental group is similar to most of the selected spike signals and can be considered as the discharge signal of the same neuron. In addition, the shaded area of the average waveform of the experimental group is smaller and the signal amplitude is larger, which further illustrates that the electrode modified with the composite coating has a higher signal-to-noise ratio.
[0099] Fig. 9 The signal-to-noise ratio of the invasive flexible neural electrode composite coating prepared in Example 2. During the 4 weeks of neural electrode implantation in the body, the signal-to-noise ratio of the blank control group was low, and it was difficult to sort out the spike signal later. The signal-to-noise ratio of the neural electrode modified with the composite coating was always higher than that of the control group, showing a trend of first rising and gradually stabilizing, and finally stabilizing at about 21.
[0100] In summary, the present invention provides a method for preparing a novel invasive flexible neural electrode composite coating, using electrospinning technology to prepare PCL-SFMA nanofibers containing the anti-inflammatory drug minocycline as a template, and in situ modifying the conductive polymer PEDOT by electrochemical deposition, followed by spin coating of SFMA hydrogel and UV curing to form a composite coating. This coating not only significantly improves the electrochemical performance of bioelectronic devices, but also effectively reduces tissue inflammatory response through the introduction of minocycline. The application of hydrogel further improves biocompatibility, reduces the adhesion of inflammatory factors and reduces Young's modulus, forming an effective buffer with brain tissue to ensure the long-term stability of the coating. In addition, the mechanically stable intermediate buffer layer structure constructed by the composite coating enhances the stimulation and recording capabilities of the electrode, achieves high charge storage / injection capacity, low interface impedance and excellent biocompatibility, and provides reliable support for long-term stable recording of dynamic single biological element signals.
[0101] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A flexible neural electrode composite coating, characterized in that: The flexible neural electrode composite coating comprises: a polymer containing an anti-inflammatory drug and methacrylylated silk protein nanofibers, the surface of the nanofibers is in-situ modified with a conductive polymer poly-3,4-ethylenedioxythiophene, and the surface of the modified material has a solidified methacrylylated silk protein hydrogel.
2. The flexible neural electrode composite coating according to claim 1, characterized in that: The anti-inflammatory drug is selected from minocycline or dexamethasone; Preferably, the polymer is selected from any one of polycaprolactone, polylactic acid or polylactic acid-co-glycolic acid or a combination of at least two thereof.
3. The method for preparing the flexible neural electrode composite coating according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) a solution containing a polymer, methacrylylated silk fibroin, and an anti-inflammatory drug is electrospun into nanofibers, which are then received on a flexible electrode surface; (2) immersing the flexible electrode having nanofibers obtained in step (1) in an electrodeposition solution containing 3,4-ethylenedioxythiophene, and performing in-situ electrodeposition by a constant potential deposition method to in-situ modify the conductive polymer poly-3,4-ethylenedioxythiophene on the surface of the nanofibers; (3) coating the surface of the in-situ modified flexible electrode obtained in step (2) with methacrylylated silk fibroin hydrogel solution and solidifying it into a gel to obtain the flexible neural electrode composite coating.
4. The preparation method according to claim 3, characterized in that: The solvent in the solution of step (1) is any one of hexafluoroisopropanol, chloroform or dimethyl sulfoxide, or a combination of at least two thereof; Preferably, the sum of the weight percentage concentrations of the polymer and the methacrylylated silk fibroin in the solution of step (1) is 11-13%.
5. The preparation method according to claim 3 or 4, characterized in that: In step (1), the mass ratio of the polymer, methacrylylated silk fibroin and anti-inflammatory drug is 5-7:5:
1. Preferably, the flexible electrode substrate material in step (1) comprises any one of polyimide, polyurethane and SU-8 or a combination of at least two thereof; Preferably, the conditions for the electrospinning in step (1) are: voltage of 16-18 kV, distance between the needle tip and the receiver of 8-12 cm, and pump speed of 0.6-0.9 mL / h.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The solvent in the electrodeposition solution in step (2) is water; Preferably, the molar concentration of 3,4-ethylenedioxythiophene in the electrodeposition solution is 0.1 mM; Preferably, the electrodeposition solution in step (2) further includes an auxiliary agent; Preferably, the auxiliary agent is selected from any one or a combination of at least two of LiClO4, polystyrene sulfonic acid or carbon nanotubes; Preferably, the molar concentration of the additive in the electrodeposition solution is 0.01-0.02 mM; Preferably, in step (2), the electrodeposition solution is prepared by ultrasonication to dissolve the solute in the solvent; Preferably, the ultrasonication time is 30-45 min.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The voltage of the in-situ electrodeposition in step (2) is 1-1.1V, and the deposition time is 100-350s.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The mass percentage concentration of methacrylylated silk fibroin in the methacrylylated silk fibroin hydrogel solution in step (3) is 12-15%; Preferably, the methacrylylated silk fibroin hydrogel solution in step (3) further comprises a photoinitiator; Preferably, the photoinitiator is selected from lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP); Preferably, the mass percentage concentration of the photoinitiator in the methacrylylated silk fibroin hydrogel solution is 0.1%; Preferably, the coating in step (3) is performed by spin coating; Preferably, the spin coating is performed at a low speed of 100-200 r / s for 5-10 s, and at a high speed of 500-700 r / s for 5-10 s.
9. A flexible neural electrode, characterized in that: The flexible neural electrode comprises a flexible electrode and a flexible neural electrode composite coating as described in claim 1 or 2 covering the outer surface of the flexible electrode.
10. Use of the flexible neural electrode composite coating or the flexible neural electrode according to claim 1 or 2 in long-term acquisition of electrophysiological signals for non-therapeutic and non-diagnostic purposes.